Offspring desertion with care? Chick mortality and plastic female desertion in Snowy Plovers. (8th March 2021) - Kupán, Krisztina; Székely, Tamás; Cruz-López, Medardo; Seymour, Keeley; Küpper, Clemens
Abstract: Offspring desertion is often a plastic behavioral strategy that requires precise timing as the termination of parental care may have profound consequences for the fitness of parents and offspring. However, the decision process involved with termination of care is still poorly understood. Snowy Plovers Charadrius nivosus show highly flexible brood care with some females deserting the brood early and re-mate, whereas others provide extended care until the young are independent. Using a dynamic modeling framework, we investigated the effect of multiple factors on the decision-making process of female brood care in Ceuta, Mexico over a 7-year period. Females were more likely to stay with larger broods, while their probability of care was lower at the beginning of the season, when re-mating opportunities are higher than later in the season. Offspring condition at hatching did not influence the length of female care. Chick death and offspring desertion frequently coincided, suggesting that deteriorating offspring condition may trigger female desertion. Females deserted broods with high survival prospects when their absence did not impact negatively chick survival. Conversely, females deserted broods with low survival prospects when chick mortality despite female care reduced the value of the brood and re-mating was still possible. This suggests that female Snowy Plovers are sensitive to the needs and the value of their broods and adjust their parental care strategy accordingly. Taken together, we conclude that offspring desertion is a highly plastic behavior that allows females to maximize their reproductive success in a stochastic environment. Abstract : Offspring desertion with care? Female Snowy Plovers carefully consider offspring survival when deciding about care continuation. These females are renowned for abandoning their families, which may suffer from chick mortality. We show that females continue care when their presence ensures brood survival. Conversely, they abandon the family and search for a new mate if their continued care does not make a difference for the brood.